Automatic Checkout Systems for Titan III and Apollo Guidance Computer Programs - Peeler, Donald L.; Meredith, Paul H.; Richards, Louis M.; Clark, Christian O. (IEEE transactions on electronic computers, 1967)
The Automatic Checkout Systems (ACS) were designed and used for the Titan III and Apollo Projects. This article describes the logical design of new approaches to program checkout and the results achieved. These checkout systems are a series of programs written for a large scale commercial computer. When a program for the airborne computer of the inertial guidance system is operated on by the ACS, it performs a symbolic simulation and generates the symbolic equations (A=B+C×D) that are performed by the airborne computer program. The ACS performs many checks for program errors in this process, indicates all areas where program analysis is required, and furnishes the program information required for analysis in optimum form. The equations generated by the ACS are manually checked against the input specification. This check is absolute in nature compared to the conventional method of analyzing the results of numerical simulations. Time consumed on the large scale commercial computer is much less than for numerical simulation.